Computation of generalized couchy integral formula for doubly connected region - Wan Nor Zaleha Amin, 1992- author; Ali Hassan, supervisor; Fakulti Sains (2015)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2015